A Concerted Transfer Hydrogenolysis: 1, 3, 2‐Diazaphospholene‐Catalyzed Hydrogenation of NN Bond with Ammonia–Borane1. (24th February 2014) - Chong, Che Chang; Hirao, Hajime; Kinjo, Rei
Abstract 1, 3, 2‐diazaphospholenes catalyze metal‐free transfer hydrogenation of a NN double bond using ammonia–borane under mild reaction conditions, thus allowing access to various hydrazine derivatives. Kinetic and computational studies revealed that the rate‐determining step involves simultaneous breakage of the BH and NH bonds of ammonia–borane. The reaction is therefore viewed as a concerted type of hydrogenolysis.